Global Nonlinear Dynamics for Engineering Design and System Safety - Lenci, Stefano; Rega, Giuseppe; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This is the first book which exploits concepts and tools of global nonlinear dynamics for bridging the gap between theoretical and practical stability of systems/structures, and for possibly enhancing the engineering design in macro-, micro- and nano-mechanics. Addressed topics include complementing theoretical and practical stability to achieve load carrying capacity; dynamical integrity for analyzing global dynamics, for interpreting/predicting experimental behavior, for getting hints towards engineering design; techniques for control of chaos; response of uncontrolled and controlled system/models in applied mechanics and structural dynamics by also considerung the effect of system imperfections; from relatively simple systems to multidimensional models representative of real world applications; potential and expected impact of global dynamics for engineering design.
Dynamic integrity: three decades of progress from macro to nano mechanics -- Dynamical integrity: a novel paradigm for evaluating load carrying capacity -- Interpreting and predicting experimental response of micro and nano devices via dynamical integrity -- Nonlinear dynamics, safety and control structures liable to interactive unstable buckling -- Local versus global dynamics and control of an AFM model in a safety perspective -- Global analysis of nonlinear dynamical systems.
Keywords: Multibody systems; Vibration; Mechanics, Applied; Engineering design; Security systems; Multibody Systems and Mechanical Vibrations; Engineering Design; Security Science and Technology